FORMULASI SEDIAAN SALEP ANTI FUNGI EKSTRAK ETANOL BAWANG PUTIH (Allium sativum) TERHADAP PERTUMBUHAN JAMUR (Tricophyton mentagrophytes) SECARA IN VITRO - Firdaus Fahdi; Herviani Sari (Jurnal Penelitian Farmasi & Herbal, 2022)
Garlic contains flavonoids, tannins, and saponins which act as antifungals. The purpose of this study was to formulate an ethanol extract of garlic (Allium sativum) ointment with various concentrations of 5%, 10%, 15% and to evaluate the ointment preparation with physical evaluation requirements. Testing the activity of the ointment preparation against the fungus Trichophyton mentagrophytes was carried out by the diffusion method. The results showed that garlic (Allium sativum) could be formulated as an antifungal ointment preparation and met the requirements of the ointment preparation evaluation test with the results of the organoleptic test of the white ointment base, the 5% formulation being pale yellow, the 10% formulation and 15% brownish yellow. The homogeneity test showed no lumps in the ointment preparation, the pH test was in accordance with the requirements, namely 4.5-6.5. The dispersion test was in accordance with the requirements, namely 5-7 cm, and the adhesive data test was in accordance with the requirements, which was more than 4 seconds. The results showed that garlic (Allium sativum) ethanol extract ointment could inhibit the fungus Trichophyton mentagrophytes where a concentration of 15% produced an inhibition zone of 10.4500 mm, and as a comparison, miconazole ointment produced an inhibition zone of 14.3833 mm.